Surface Limited Redox Replacement Deposition of Platinum Ultrathin Films on Gold: Thickness and Structure Dependent Activity towards the Carbon Monoxide and Formic Acid Oxidation reactions. (20th August 2016) - Al Amri, Zakiya; Mercer, Michael P.; Vasiljevic, Natasa
Abstract: The Surface Limited Redox Replacement (SLRR) method in one-cell configuration has been used to grow Pt ultra-thin films on Au using two different sacrificial underpotentially deposited (UPD) layers: Cu and Pb. The Pt films grown by multiple Pb UPD-SLRR cycles (1–10) exhibit comparable roughness as determined by integration of the H UPD charge. In contrast to that, due to the 2:1 stoichiometry of the replacement between Cu UPD layer and PtCl4 2+ ions, the Pt films grown by Cu UPD-SLRR show a steady increase of the roughness with the number of deposition cycles (1–10). The differences in the structure of the films have been used as a platform to study the stripping of pre-adsorbed CO and the formic acid oxidation (FAO) reaction as a function of their thickness. On Pt films of comparable roughness grown by SLRR of Pb UPD, the CO stripping peak shows no significant changes in the onset potential and a small peak maximum shift of ∼7 mV between the film of lowest (1 ML) and all higher thicknesses (2–10 ML). However, Pt films grown by SLRR of Cu UPD show a larger potential window of differences of ∼26 mV over which the peak maximum potentials shift more negative with the number of deposition cycles. The most positive CO stripping potential obtained for a sub-ML Pt (∼0.56 ML) grown by a single SLRR cycle suggests CO is more strongly bonded than on films grown by multiple replacements that completely cover the Au substrate. The measured activity toward FAO is in agreement with the CO electro-oxidation results. No significant differences in the activity for FAO have been observed on Pt films of comparable roughness grown by SLRR of Pb UPD which show activity close to that of pure Pt. However, a more significant change of FAO reactivity has been measured for Pt films grown via SLRR of Cu UPD with the highest activity measured for a sub-ML Pt deposit. Following subsequent replacements, the FAO activity tends towards that of pure Pt. The observed differences in the catalytic behaviour of Pt films grown by SLRR are the result of the differences in their morphology and the nanocluster structure of the films. On sub-monolayer Pt films, the behaviour is dominated by nanocluster size and coverage of the deposit. For a completely covered surface of Au, the effect of roughness of Pt films and nanocluster nature of the deposit has a dominant role in the behaviour and activity.